MetroBeta: beta spectrometry with metallic magnetic calorimeters in the framework of the European program of ionizing radiation metrology - Loidl, Martin; Beyer, J.; Bockhorn, L.; Enss, Christian; Györi, D.; Kempf, Sebastian; Kossert, K.; Mariam, R.; Nähle, O.; Paulsen, M.; Rodrigues, M.; Schmidt, M. (Journal of low temperature physics, 2018)
MetroBeta is a European project aiming at the improvement of the knowledge of the shapes of beta spectra, both in terms of theoretical calculations and measurements. It is part of a common European program of ionizing radiation metrology. Metallic magnetic calorimeters (MMCs) with the beta emitter embedded in the absorber have in the past proven to be among the best beta spectrometers, in particular for low-energy beta transitions. Within this project, new designs of MMCs optimized for five different beta energy ranges were developed. A new detector module with thermal decoupling of MMC and SQUID chips was designed. An important aspect of the research and development concerns the source/absorber preparation techniques. Four beta spectra with maximum energies ranging from 76 to 709 keV will be measured. Improved theoretical calculation methods and complementary measurement techniques complete the project.
Gesehen am 28.02.2020